(untitled) (Research, Society and Development, 2021)
This research work analyzes the need for state intervention to protect small businesses as one of the measures to overcome unemployment caused by economic crises, especially the one that broke out in 2008. In Brazil, there are currently about 6.4 millions of commercial establishments. Of this total, 99% are small companies, accounting for 52% of formal jobs in the private sector. However, despite its unquestionable importance, we must highlight its low survival rate, on average 58% compared to small companies with up to 2 years. We will verify the role and the limits of the State’s action in times of crisis and in the protection of this under-sufficient segment, passing through the analysis of the premise that economic growth is a sufficient condition for achieving development and overcoming high unemployment rates. To respond to the problems raised, historicity will be used to verify the increase in the rate of entrepreneurship after the outbreak of the 2008 crisis, also using the economic analysis of law in an attempt to situate the need for state action in promoting and implementing different legal treatment of these categories. Finally, it is hypothesized whether the implementation of the constitutional principle of differentiated treatment of small businesses can be used as one of the tools to combat unemployment in times of economic crisis.